Namibia and the common monetary area : costs, benefits and choices - Eita, Joel Hinaunye (School of Economics, 2023)
This study analyses if the Common Monetary Area 1s an optimum currency area for Namibia. It analyses if Namibia should continue its membership of the Common Monetary Area or whether it should consider alternative exchange rate regimes. The analysis was done in terms of the theory of optimum currency areas. The traditional theory of optimum currency areas points labour mobility, openness, diversification, intensity of mutual trade, financial and goods market integration, wage flexibility and symmetry and asymmetry of shocks as important criteria for optimum currency area. The new theory of optimum criteria points generalised purchasing power parity hypothesis, time inconsistency and the issue of nominal anchor as criteria for optimum currency area. Elimination of transaction costs, savings on foreign exchange reserves, reduction of exchange rate uncertainty are identified as important benefits from using a common currency, while the loss of seigniorage revenue, real exchange rate misalignment, impact of exports on employment are identified as the most visible costs associated with using a common currency. All criteria, benefits and costs were analysed. The results suggest that Namibia should not withdraw from the CMA, but should continue its membership and encourage negotiations for a full monetary union. That is because although the economy of Namibia is not well diversified and there is no labour mobility between Namibia and South Africa, there is a high degree of financial and goods markets integration, high intensity of mutual trade between Namibia and South Africa, and high degree of openness of Namibia's economy. The analysis of purchasing power parity hypothesis shows that the real exchange rates of Namibia and South Africa are cointegrated, and the shocks to the two economies are symmetric suggesting that the two countries require similar policy response. Analysis of the benefits and costs also shows that the benefits are far high than the costs. There are significant gains from the elimination of transaction costs, and savings on foreign exchange reserves. The impact of real exchange misalignment on measures of economic performance as well as the impact of exports on 2 employment is very weak. This weak impact of real exchange rate misalignments on measures of economic performance, and also weak impact of exports on employment as well as the symmetry of shocks of Namibia and South Africa as indicated by the Bayoumi-Eichengreen model suggest that Namibia should continue its membership of the Common Monetary Area. The symmetry of shocks of Namibia and South Africa suggests that the Common Monetary Area is still optimum currency area because these two countries require similar policy response.